A numerical approach to estimate the tensile strength of structural lightweight concrete - Tugrul Tunc, Esra; Alyamac, Kursat Esat; Ulucan, Zulfu Cinar (TUBITAK, 2020)
Since lightweight concrete has many advantages over traditional concrete, it is of great importance for the building industry to investigate more and examine its mechanical properties. It is considered that it will be very useful to use lightweight concretes in special concrete classes if they have sufficient strength properties. Structural lightweight concrete can be produced from different lightweight aggregates. Expanded clay aggregate, which is one of them, is thought to have an important place in the production of structural light concrete with its high reserve and easy availability. At the same time, structural lightweight concrete can improve the properties of structures such as earthquake resistance and thermal insulation. The aim of this study; a series of concrete specimens produced with different mixing ratios containing lightweight expanded clay aggregate is to develop a numerical model using the tensile strength test results in the literature. For this purpose, the studies on structural lightweight concrete have been investigated in detail in the literature. With this numerical model, it is hoped that the tensile strength can be easily calculated depending on the content of cement, aggregate, powder/filler, silica fume, water, lightweight expanded clay aggregate and superplasticizer. In this context, the parameters affecting tensile strength were determined. The effects of these parameters on tensile strength were interpreted with related graphics. In the numerical model developed in this study, tensile strength affected by the related parameters is included as output. As a result; with the numerical model developed using nonlinear statistical analysis, it is planned to develop a practical equation with high precision that can be easily used by application engineers. © 2020, TUBITAK. All rights reserved.
Yapısal hafif betonun çekme dayanımına sayısal bir yaklaşım
Keywords: A numerical model; Lightweight expanded clay aggregate; Structural lightweight concrete; Tensile strength